Metformin ameliorates diabetic nephropathy in a rat model of low-dose streptozotocin-induced diabetes - Zhang, Siwei (Exp Ther Med, 2017)
The present study aimed to explore the renoprotective effect of metformin on diabetic nephropathy in type 2 diabetic rats. A rat model of type 2 diabetic nephropathy (T2DN) was successfully induced via a high-fat diet combined with a single low-dose of streptozotocin. Metformin was administered intragastrically for 13 weeks, and fasting blood glucose (FBG), total cholesterol (TC), triglycerides (TG), HDL-c, LDL-c, urinary and serum creatinine levels were subsequently examined at the end of administration. Renal function was determined after the treatment protocol. Expression levels of transforming growth factor (TGF)-β1 and connective tissue growth factor (CTGF) were assessed via immunohistochemical analysis. Superoxide dismutase activity, malondialdehyde content and glutathione peroxidase levels were assessed in kidney tissues using commercially available kits. The results of the present study demonstrated that metformin administration significantly decreased the levels of serum blood urea nitrogen, serum creatinine, creatinine clearance, urinary albumin excretion and fasting blood glucose in rats with T2DN. Furthermore, TG, TC and LDL-c levels were significantly decreased following metformin treatment, whereas HDL-c was increased. Metformin treatment significantly increased SOD activity and significantly decreased malondialdehyde levels, as compared with the model group. It was also demonstrated that metformin administration significantly decreased the expression levels of TGF-β1 and attenuated the morphological changes associated with T2DN in rats. These data clearly demonstrated the renoprotective effects of metformin against the development and progression of T2DN in rats. The underlying mechanism of this protective effect may be associated with glycemic control, lipid metabolism, and anti-oxidative and anti-inflammatory functions.